Arabic Language Learning Support Using the Singing Method at Muslimeen Care Academy Selangor - Aprilya Laras Dewi Sinta (Al-Jawhar : Journal of Arabic Language, 2026)
The international community service program organized by Ithla Abroad ASEAN was attended by thirty participants from various PTKINs in Indonesia, including five fifth-semester students from the Arabic Language Education Program at the State Islamic University of Palangka Raya. The program focused on developing a fun-learning-based Arabic language curriculum to introduce the language to children and expand their foundational understanding. This activity employed a qualitative approach using the service-learning method, which included preparation, mentoring, and practical implementation phases, where students served as facilitators who designed activity steps and provided direct guidance to participants. Data collection was conducted through observation, interviews, and documentation, enabling a comprehensive analysis of the mentoring process. The results of the activity showed an increase in the children’s knowledge of the Arabic language through educational songs, an expansion of their mastery of simple vocabulary related to daily greetings, increased motivation and learning ability through the singing method, and the acquisition of a basic foundation in Arabic that can support them in participating in competitions or other activities related to the Arabic language.